2011
DOI: 10.1073/pnas.1105781108
|View full text |Cite
|
Sign up to set email alerts
|

Active transport, substrate specificity, and methylation of Hg(II) in anaerobic bacteria

Abstract: The formation of methylmercury (MeHg), which is biomagnified in aquatic food chains and poses a risk to human health, is effected by some iron-and sulfate-reducing bacteria (FeRB and SRB) in anaerobic environments. However, very little is known regarding the mechanism of uptake of inorganic Hg by these organisms, in part because of the inherent difficulty in measuring the intracellular Hg concentration. By using the FeRB Geobacter sulfurreducens and the SRB Desulfovibrio desulfuricans ND132 as model organisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
423
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(461 citation statements)
references
References 33 publications
27
423
3
2
Order By: Relevance
“…It has been revealed that Hg(II) uptake in anaerobic bacteria is an active transport process requiring energy and not a passive process as commonly perceived (Schaefer et al 2011). The question can be asked whether cellular Hg uptake is specific for Hg(II), or accidental, occurring via some essential metal importer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that Hg(II) uptake in anaerobic bacteria is an active transport process requiring energy and not a passive process as commonly perceived (Schaefer et al 2011). The question can be asked whether cellular Hg uptake is specific for Hg(II), or accidental, occurring via some essential metal importer.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic mercury (Hg 2+ ) can be transformed into highly neurotoxic methylmercury (MeHg) via microbial processes that involve sulfate or iron reduction in anaerobic environments (Pak and Bartha 1998;Schaefer et al 2011;Yu et al 2012;Hsu-Kim et al 2013). Most Hg in soil is detected as ionic Hg 2+ species and shows relatively low toxicity, however, it still poses some environmental risk due to potential for Hg methylation followed by bioamplification in soilplant systems (Meng et al 2010;Liu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, legacy Hg deposits currently sequestered in sediments, wetland soils, permafrost, and forests may become mobile under a number of scenarios such as forest fires, and the disturbance of soils, sediment, and permafrost, thus increasing the inorganic Hg available for MeHg production. However, the uptake of this critical substrate has been found to be limiting in the methylation process, especially in the absences of certain complexing thiols (Schaefer et al 2011). Hsu-Kim et al (2013b provide an excellent review of the factors controlling bioavailable Hg and summarize four main hypotheses for the uptake through both outer and inner membranes.…”
Section: Bioavailability Of Hgmentioning
confidence: 99%